2007
DOI: 10.1002/j.2161-0045.2007.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Choices and Challenges: A Qualitative Exploration of Professional Women's Career Patterns

Abstract: With the rapid changes occurring in the role of work in women's lives, this research project was designed to examine the career planning, career decision making, and work history of women in both female-dominated and gender-neutral careers (U.S. Department of Labor, n.d.-a). A qualitative analysis of structured interviews identified 6 emerging themes: variations of career/family patterns, career encouragers, career obstacles, personal compromises, career changes, and career decision-making patterns. Insights f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 25 publications
2
71
0
1
Order By: Relevance
“…Sewell, Hauser, and Wolf (1980) found that having family negatively impacted women's careers but not men's. A qualitative analysis of women's careers found that women often choose careers, which allow greater flexibility in work family conflict (Whitmarsh, Brown, Cooper, Hawkins-Rodgers, & Wentworth, 2007). Whitmarsh et al (2007) found that women plan pregnancy and other family events around work schedules, and in turn, report difficulties in trying to maintain both family and career responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Sewell, Hauser, and Wolf (1980) found that having family negatively impacted women's careers but not men's. A qualitative analysis of women's careers found that women often choose careers, which allow greater flexibility in work family conflict (Whitmarsh, Brown, Cooper, Hawkins-Rodgers, & Wentworth, 2007). Whitmarsh et al (2007) found that women plan pregnancy and other family events around work schedules, and in turn, report difficulties in trying to maintain both family and career responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that addressed the career planning, career decision making, and work history of women in both female-dominated and gender-neutral careers, Whitmarsh (2007) found that women in the female-dominated group of that study experienced positive reinforcement for their career choices from family members, while those in the gender-neutral group experienced support and mentoring from outside the family. Like the participants in the current study, the participants in the female-dominated group of that study did not identify any significant obstacles to career advancement.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the studies reviewed in this section were qualitative in nature (Kuo-Rice, 2005;Madsen, 2007aMadsen, , 2007bMayer, 2001;Whitmarsh, 2007), and others were quantitative (ACHE, 2002;Courtney et al, 2001;Lane, 1998). The results of both types of studies showed, researchers can agree on the barriers to career advancement of women.…”
Section: Overall Barriers and Facilitators To Career Development Of Wmentioning
confidence: 92%
See 1 more Smart Citation
“…As such, barriers and supports (Table 4) play an influential role in the careers of women in intercollegiate athletics. (Albert & Luzzo, 1999;Astin, 1984;Betz & Fitzgerald, 1987;Lent et aI., 1994;Savickas, 2002) Sagas & Cunningham, 2004;Whitmarsh, 2007). Additionally, Kanter (1977) suggested that the primary function of a mentor was "to make introductions or train a young person to move effectively through the system" (p. 181).…”
Section: Supports and Barriers To Career Developmentmentioning
confidence: 99%